Iceland : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Rapid growth during the second half of the 1990s led to overheating and the emergence of financial vulnerabilities by the end of the decade. Over the medium term, investment projects will impart a significant impetus to economic activity, and output will grow for some years above its long-term trend pace. There are, however, significant upside risks to this medium-term central scenario. Executive Directors supported the authorities' view that macroeconomic policies would have to remain restrictive to counteract the expected demand pressures over the medium term.